2022
DOI: 10.3390/resources11050046
|View full text |Cite
|
Sign up to set email alerts
|

The Key to Sustainable Economic Development: A Triple Bottom Line Approach

Abstract: Concerns about improving social, environmental, and economic living standards are the basis of the triple bottom line (TBL) link to economic development (ED). Aware of the importance of studying their relationship, this article analysed the influence of TBL on ED. A quantitative methodology was used. The sample comprised a panel of data from 2006 to 2019 for OECD (Organisation for Economic Co-operation and Development) countries. Five multiple linear regression models were estimated by the generalised method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 154 publications
0
9
0
Order By: Relevance
“…Lock and Araujo [85], in their study using automated content analysis of the most profitable European corporations' websites in the domain of applying the triple bottom line concept, came to the conclusion that there is a clear dominance of the economic dimension and profit orientation, while a greater interest was recorded in environmentally sensitive industries for the social dimension compared to other industries. An additional support for the application of the TBL criterion is given by the results of the study by Nogueira et al [86], who revealed that the social dimension is positively related to economic development, while the environmental dimension negatively affects it and the economic dimension has conflicting synergies. The practical implementation has validated deficiencies that were identified throughout the theoretical development and scientific study of the concept.…”
Section: Discussionmentioning
confidence: 97%
“…Lock and Araujo [85], in their study using automated content analysis of the most profitable European corporations' websites in the domain of applying the triple bottom line concept, came to the conclusion that there is a clear dominance of the economic dimension and profit orientation, while a greater interest was recorded in environmentally sensitive industries for the social dimension compared to other industries. An additional support for the application of the TBL criterion is given by the results of the study by Nogueira et al [86], who revealed that the social dimension is positively related to economic development, while the environmental dimension negatively affects it and the economic dimension has conflicting synergies. The practical implementation has validated deficiencies that were identified throughout the theoretical development and scientific study of the concept.…”
Section: Discussionmentioning
confidence: 97%
“…Sustainable development involves balancing three dimensions, also known as the three economic, social and environmental bottom lines. These three aspects are interdependent and must be balanced to achieve sustainable development (Hammer & Pivo, 2016;Nogueira et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the growing body of literature on microfinance and economic development, there remains a dearth of comprehensive bibliometric studies that systematically analyze the scholarly discourse in this field. Existing reviews and meta-analyses tend to focus on specific aspects of microfinance or particular geographic regions, overlooking the broader trends and patterns in the literature [15]- [19]. Consequently, there is a need for a rigorous bibliometric study that synthesizes the vast array of research on microfinance and economic development initiatives, offering valuable insights for policymakers, practitioners, and researchers alike.…”
Section: Introductionmentioning
confidence: 99%